The dark side of diversification: Passive finance and fossil-fuel investment - Johannes Lundberg (Finance and Society)
What shapes fossil-fuel investment and divestment decisions? What are pension funds’ climate-related considerations? And how do conceptions of portfolio risk influence these issues? Danish pension funds constitute a rare and understudied cohort of investors who have undertaken comparatively progressive fossil-fuel investment decisions. Simultaneously, diversification and market rationality have frequently been invoked as obstacles to divestment and active ownership. Using the Danish experience, this article conducts an archaeological analysis of the concept of portfolio risk, unearthing the various ways in which it has shaped fossil-fuel investment decisions. The analysis identifies five key aspects through which the concept has hampered Danish pension funds’ active ownership and fossil-fuel divestment decisions (sector diversification, externalities, market rationality, dispersed ownership, and passive index investing). The article argues that these discursive aspects have reinforced a passive tendency within finance capitalism to bolster the status quo, thereby supporting prevailing market actors and the continued extraction of fossil fuels.